Accuracy in trait judgments based on WeChat: Detecting who stands on the extreme levels of the big-five trait continua. (April 2021) - Wu, Wenjie; Mitchell, Peter; Zheng, Jianhong; Chen, Shiyao
Abstract: Trait inferences occur not only during social interaction but also in virtual environments. Previous research suggested social media owners (targets) revealed their real but not idealized personality traits online, based on which people were to some extent able to make accurate judgments of the big-five traits of the targets. In the present research, participants made inferences of different levels of targets' big-five traits (low, meddle or high) after briefly browsing scant information of the unacquainted WeChat owners. Results demonstrated that participants were not uniformly accurate in judging each level of each of the big-five traits; they were prone to be accurate when judging a target located on the extremes (low or high) of the traits, but were less accurate when judging a target located at the average level. These findings extend previous results from real-world scenarios revealing people's ability to perceive other persons based on subtle signals in the domain of social media.